Getting To The Bottom Of The Well: The Value Of Qualitative Research Into Teaching And Learning - Cousin, Glynis (Critical Studies in Teaching and Learning, 2023)
Qualitative researchers are often compelled to defend their methods and associated underpinning philosophy to researchers from other cultures of inquiry. This is particularly so where academics from a variety of disciplines are undertaking research into teaching and learning from a non-social scientific background. This article examines how we might best mount a defence of the qualitative tradition for teaching and learning research through the identification of:a) the commonalities between quantitative and qualitative research approaches; b) the relation between qualitative research and the humanities; and c) the distinctiveness of qualitative research. In discussing these issues I address reservations often expressed by those who are sceptical of the value of qualitative research, proposing Â that a fruitful way of explicating this value is to draw attention to affinities across cultures of inquiry.